3D Printed Biomimetic PCL Scaffold as Framework Interspersed With Collagen for Long Segment Tracheal Replacement - She, Yunlang; Fan, Ziwen; Wang, Long; Li, Yinze; Sun, Weiyan; Tang, Hai; Zhang, Lei; Wu, Liang; Zheng, Hui; Chen, Chang (Frontiers in Cell and Developmental Biology, 2021)
The rapid development of tissue engineering technology has provided new methods for tracheal replacement. However, none of the previously developed biomimetic tracheas exhibit both the anatomy (separated-ring structure) and mechanical behavior (radial rigidity and longitudinal flexibility) mimicking those of native trachea, which greatly restricts their clinical application. Herein, we propose a biomimetic scaffold with a separated-ring structure: a polycaprolactone (PCL) scaffold with a ring-hollow alternating structure was three-dimensionally-printed as a framework, and collagen sponge was embedded in the hollows amid the PCL rings by pouring followed by lyophilization. The biomimetic scaffold exhibited bionic radial rigidity based on compressive tests and longitudinal flexibility based on three-point bending tests. Furthermore, the biomimetic scaffold was recolonized by chondrocytes and developed tracheal cartilage in vitro. In vivo experiments showed substantial deposition of tracheal cartilage and formation of a biomimetic trachea mimicking the native trachea both structurally and mechanically. Finally, a long-segment tracheal replacement experiment in a rabbit model showed that the engineered biomimetic trachea elicited a satisfactory repair outcome. These results highlight the advantage of a biomimetic trachea with a separated-ring structure that mimics the native trachea both structurally and mechanically and demonstrates its promise in repairing long-segment tracheal defects.